Тихий Дон: [роман] (Михаил Шолохов) - Шолохов Михаил Александрович (Азбука-классика, 2018)
Экземпляры: Ф. 10 (20220525) / Инвентарный номер: 49178 / Цена: 130.00 / Сис.шифр: Р2 / Авт.знак: Ш 78 / ГРНТИ: 17.82 / ББК: 84(2=411.2)6